Implementasi Algoritma Colussi Pencocokan Kata Berbahasa Inggris Pada Dokumen Microsoft Office Word - Ahmad Ardianto (Journal of Information System Research (JOSH), 2021)
English words are often used in various documents including one of them is in Microsoft Office Word documents. A data or document may experience errors, namely in foreign words that do not match the true meaning or meaning so that the document cannot be used. To get the correct document results and foreign words that match the meaning, this is done by using the Colossi algorithm by matching these foreign words. The colossi algorithm shifts the text from left to right. The colossi algorithm has two stages of its completion. First Comparisons are made from left to right on text which is located in the same position as the pattern position where the value of the function kmp "ext is slightly greater than -1. These positions are called nohole (s), second Comparing the remaining positions (other names are hole (s)) from the left to the right. With this algorithm it is expected to solve the problem of foreign words in Microsoft office Word documents. , then the application is built using Microsoft Visual Basic 2008, and it is expected that the results of the application can produce the right document